Risk of cancer after anticoagulation in patients with unprovoked venous thromboembolism: an observational cohort study. (18th May 2017) - Eischer, L.; Kammer, M.; Traby, L.; Kyrle, P. A.; Eichinger, S.
Abstract : Essentials Data on long‐term cancer risk are controversial in patients with venous thromboembolism (VTE). We assessed long‐term rates and risk factors of cancer in patients with VTE. Cancer risk after anticoagulation is not higher in VTE patients than in the general population. VTE recurrence is not predictive of a future cancer diagnosis. Summary: Background: Patients with venous thromboembolism (VTE) are at risk of having a subsequent cancer diagnosis. The risk is highest during the first 6 months. Reports on cancer rates thereafter are controversial. We aimed to assess long‐term rates and risk factors of cancer in patients with VTE. Methods and Results: We followed patients with a first unprovoked VTE after discontinuation of anticoagulation, and excluded those receiving long‐term antithrombotic therapy or with major thrombophilia. The study endpoint was the occurrence of cancer. Sixty‐two (5.2%) of 1188 patients developed cancer during a median follow‐up of 98 months. The cumulative incidence rates of cancer were 0.7% (95% confidence interval [CI] 0.2–1.2%), 3.1% (95% CI 2.0–4.1%) and 9% (95% CI 6.5–11.5) after 1, 5 and 15 years; these were not significantly different from those in the matched general population (0.6%, 3.4%, and 12.2%, respectively). The corresponding standardized incidence ratios (ratio of the observed cancer cases and the number of cases based on national cancer incidence rates) of 1.1 (95% CI 0.5–2.5), 1.0 (95% CI 0.6–1.4) and 0.9 (95% CI 0.7–1.2) did not indicate a difference in cancer incidence between our cohort and the general population. Advancing age (hazard ratio [HR] per decade 1.5, 95% CI 1.2–2.0) and shorter duration of anticoagulation (HR per 1‐month decrease 1.3, 95% CI 1.1–1.6) were associated with an increased cancer risk, whereas VTE recurrence was not (HR 1.17, 95% CI 0.66–2.07). Conclusions: Asymptomatic patients with unprovoked VTE who have completed anticoagulation therapy do not have a higher cancer risk. The inverse association between the duration of anticoagulation and the incidence of cancer warrants further investigation.